Performance of Network Real-Time Kinematic in Hydrographic Surveying - Mohamed Elsayed Elsobeiey (Journal of Marine Science and Engineering)
The main objective of this paper is to investigate the performance of the Network Real-time Kinematic (NRTK) technique in hydrographic surveying and check whether it meets the International Hydrography Organization (IHO) minimum bathymetry standards for the safety of navigation hydrographic surveys. To this end, the KAU-Hydrography 2 vessel was used to conduct a hydrographic survey session at Sharm Obhur. NRTK corrections were streamed in real time from the KSA-CORS NTRIP server and GNSS data were collected at the same time at the base station using a Trimble SPS855 GNSS receiver. Multibeam records were collected using a Teledyne RESON SeaBat T50-P multibeam echosounder in addition to Valeport’s sound velocity profiler records and Applanix POSMV data. Applanix POSPac MMS 8.3 software was used to process the GNSS data of the base station along with the POSMV data to obtain the Smoothed Best Estimate of Trajectory (SBET) file, which is used as a reference solution. The NRTK solution is then compared with the reference solution. It is shown that the Total Horizontal Uncertainty (THU) and the Total Vertical Uncertainty (TVU) of the NRTK solution are 6.38 cm and 3.10 cm, respectively. Statistical analysis of the differences between the seabed surface generated using the NRTK solution and the seabed surface generated using the Post-Processed Kinematic (PPK) technique showed an average of −0.19 cm and a standard deviation of 2.4 cm. From these results, we can conclude that the KSA-CORS NRTK solution successfully meets IHO minimum bathymetry standards for the safety of navigation hydrographic surveys at a 95% confidence level for all orders of hydrographic surveys.